New fair QoS-based charging solution for mobile multimedia streams. (14th February 2008) - Butyka, Zsolt; Jursonovics, Tamas; Imre, Sandor
In this paper, we present a new streaming proxy based charging architecture for QoS differentiated charging in 3G. We give a short overview of charging concepts in next generation mobile networks and we describe the most important network attributes on which the quality depends. Our goal is to point out the importance of bursty packet loss which determines the quality of the multimedia streaming in contrast with the average loss rate. We propose several methods for QoS differentiated charging which are in compliance with the recommendations of 3GPP. We describe three models which can predict the QoS of a stream. The algorithms are evaluated on a real GPRS streaming flow.